O papel dos esquemas para a compreensão de leitura em espanhol - Oliveira, Maria Laura de (2005)
This research makes some observations into the reading in Spanish as a foreign language within classes of a regular school. In this study reading is considered a cognitive process whereby the representation of the meaning is built in the reader s mind through his/her own knowledge and the information from the text. Specifically, the main objective of this study is to verify the role played by schemata as the representation of knowledge during the reading process. We also intend to analyze the importance of some cultural aspects in the schemata construction in reading comprehension. Thus, we developed an empirical research working with two different groups, an experimental and the control one, in order to verify the hypotheses arisen in this work. The subjects of this work are the students that have already finished high school and at the moment they have been preparing themselves to go to university. In this context the students have studied Spanish as a foreign language just to be succeed in their university exams. The instruments used to collect the data were a questionnaire, a pre-test and a reading comprehension test applied to both groups. Theoretical support was based on reading theory as well as schemata theory as the representation of meaning used in reading comprehension. After analyzing the data we found out that schemata really interfere in reading comprehension. The experimental group that was given some information about cultural aspects before reading the text got a better score than the control group that was not given the same information. So, we hope that this work might contribute to reading comprehension and also helps to find out good instruments to develop this activity in teaching/learning contexts.